Rolls-Royce Civil Aerospace Supplier Engineered Equipment Configuration Integration - Moreno Sanchez, Marlen (2016)
The strategic priorities of Rolls-Royce PLC from 2016 onwards highlight engineering excellence, Operational excellence in lean manufacturing and supply chain, improving processes and lowering costs and to influence project knowledge and engineering capabilities.